The Use of Audiovisual Media in Physical Education Learning to Improve Student Learning Outcomes: A Systematic Literature Review - Rizqullah Al Yassar; Guntur Yulisatria; Yopi Hutomo Bhakti; Mela Suhariyanti (Journal for Lesson and Learning Studies, 2025)
Learning media play a crucial role in enhancing instructional effectiveness, particularly in physical education, which requires understanding movement concepts and mastering physical skills. However, the limited use of audiovisual media leads to weak conceptual understanding, low motivation, and suboptimal student learning outcomes. This study aims to systematically analyze the effectiveness of audiovisual media in improving student learning outcomes in Physical Education, Sports, and Health. The study employs a Systematic Literature Review method, using data sources from scientific articles published over the last five years. Data were collected through a search of the Google Scholar database and selected based on established inclusion and exclusion criteria. A total of twelve articles were analyzed using a qualitative descriptive approach through coding and synthesis of research findings. The results indicate that the use of audiovisual media consistently has a positive impact on students’ learning engagement, understanding of movement concepts, and mastery of motor skills in physical education learning. Audiovisual media has proven effective in facilitating technique visualization, clarifying abstract material, and increasing learning motivation. The findings confirm that the integration of audiovisual media is a relevant and effective instructional strategy and highlights the need to strengthen teachers’ competencies in developing and implementing audiovisual media–based learning to sustainably improve the quality of physical education learning processes and outcomes.